Innovation in Medical Disinfection: Design and Automation of an Intelligent Cabin for Pathogen Elimination with Logosoft in High-Complexity Clinics - Barcelli, Jonatan; Quispe, Ruben (LACCEI, 2025)
The disinfection of medical equipment became a highly demanded task following the 2020 pandemic due to the rapid spread of SARS-CoV-2. Various companies implemented rudimentary models of disinfection cabins and manual temperature monitoring for customers, accompanied by the abundant use of 70% medicinal alcohol. However, challenges arose, such as accidental application to the eyes causing irritation. With the wave of infections, many clinics experienced a high influx of patients, leaving them overwhelmed and exposed to contracting other pathogens in the environment. In response to this problem and the surge in infections, this thesis aims to design an automated cabin for pathogen elimination in clinical environments, specifically targeting clinical equipment in direct contact with patients and medical staff. To achieve automation, a process control program was required; Logosoft was chosen for its ease of use, compactness, and ability to display failure alerts on its built-in screen. The methodology used is quantitative-experimental in nature, given its trial-and-error approach to find efficient values that optimize the disinfection system. The results obtained are positive, demonstrating improvements in disinfection processes, with the only variation being the adjustment of the solution’s concentration. However, the project seeks to integrate these independent processes to achieve better results with safer quantities and shorter processing times. From this study, it can be concluded that although the disinfection process is not entirely comprehensive, it can achieve results very close to those of a full sterilization process.